2016
DOI: 10.1016/j.aju.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ureteric stone size, on bone window versus standard soft-tissue window settings, on multi-detector non-contrast computed tomography

Abstract: ObjectiveTo compare the difference in mean stone size, as measured on bone window vs standard soft-tissue window setting using multi-detector computed tomography (MDCT) in patients with a solitary ureteric stone.Patients and methodsIn all, 60 patients presenting to the emergency and outpatient departments of a University Hospital from May 2015 to October 2015 and fulfilling the inclusion criteria were included in the study. A 64-slice MDCT was used to assess the locations and size of the ureteric stones. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Urolithiasis is considered as one of the most common causatives of admission to the emergency and urology outpatient departments 1. Recent studies have shown an increase in the incidence and prevalence of urolithiasis worldwide 2.…”
Section: Introductionmentioning
confidence: 99%
“…Urolithiasis is considered as one of the most common causatives of admission to the emergency and urology outpatient departments 1. Recent studies have shown an increase in the incidence and prevalence of urolithiasis worldwide 2.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being a small study (n = 24), a major strength was that only stones that had spontaneously discharged were included allowing for manual measurement. Another study compared ureteral stone measurements in 60 patients using both the soft tissue and bone windows in multidetector CT [15]. The average stone size in the bone window was 4.8 mm, while in the soft tissue window, it was 6.68 mm.…”
Section: Discussionmentioning
confidence: 99%
“…3 The stone site has a major impact on the symptoms of acute renal colic. 4 Over decades, great advances have been made in the minimally invasive treatment of ureteral stones. [5][6][7] Recent therapeutic options include transurethral lithotripsy (TUL) by holmium laser, extracorporeal shock wave lithotripsy (ESWL) for proximal ureteral stones, and laparoscopic lithotripsy.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Stone removal with ureteroscope is most effective in treating lower ureteral stones. 4 In the setting of acute ureteral colic, ureteral spasms make the passage of the guide wire of the ureteroscope difficult. 5 However, applying local lidocaine gel, aminophylline 5%, or intravenous Buscopan® can reduce ureteral spasms and increase the rate of successful ureteroscopy.…”
Section: Introductionmentioning
confidence: 99%